Konsep Kebebasan Beragama dalam al-Qur’an: Penafsiran Imam al-Qurthubi - Hasan Hasan; Nur Isyanto (Al Ashriyyah, 2022)
The issue of religious pluralism is still understood in the context of a single religious relationship. The plurality that exists in this world, including the plurality of beliefs, is a sunnatullah that cannot be denied. Religion, no matter how sure and how strong we embrace it, cannot be a reason to insult and bring down other religions. This study aims to 1) analyze the construction of interpretation of Imam al-Qurtubi in interpreting verses related to freedom of religion in the Qur'an. 2) analyze the implementation of the concept of religious freedom in the Indonesian context. The method used in this study is a qualitative method with the type of library research (library research). The results of the study show that the interpretation of Imam Al-Qurthubi in interpreting verses related to freedom of religion is that it is not permissible for anyone to force someone to embrace Islam. In terms of interpretation of the verses on freedom of religion, al-Qurthubi uses the method of interpreting verse bil verse, namely interpreting one verse with another verse of the Koran. al-Qurthubi in interpreting al-din as "faith and religion". In addition, Imam al-Qurtubi in interpreting is more likely to provide an understanding regarding the asbab al-nuzul verse.